Manajemen Bahan Ajar Menulis Puisi Pada Tadris Bahasa Indonesia IAIN Curup - Murni Yanto (Tadbir : Jurnal Studi Manajemen Pendidikan, 2020)
This study aims to explain and analyze about how the management of teaching material poetry’s writing in Tadris Bahasa Indonesia at IAIN Curup. As well as knowing curriculum management in improving the teaching material of writing poetry in Tadris Bahasa Indonesia at IAIN Curup. The results of this research are expected to be able to contribute thoughts in an effort to improve quality education and increase knowledge about the management of teaching material poetry’s writing in Tadris Bahasa Indonesia at IAIN Curup. This study uses a development approach. Data collections was carried out using questionnaires, interviews and tests. To obtain information on the feasibility of teaching materials, a validation test was carried out on the material eligibility about language (poetry). The subjects of this study were 22 students. Based on the analysis, poetry writing teaching materials can be categorized as good and appropriate to be used. Students have diverse needs in writing poetry. The need for aspects of the content and physical aspects of teaching materials. Entertaining teaching materials as well as clear and varied poetry, exercises and evaluations in accordance with the theme desired by student. Teaching materials such as modeling the making of poetry and presenting images are needed to motivate students in carrying out exercises and evaluating poetry writing varied examples of poetry. Teaching material for writing poetry entitled fun writing poetry used in learning. Teaching material development in the form of textbooks can improve student’s abilities. So the management of writing poetry can improve students, understanding of writing poetry.